METODE DEDICATED STORAGE FIFO UNTUK BAHAN BAKU BERKUALITAS PADA PT FRISIAN FLAG INDONESIA PLANT PASAR REBO JAKARTA TIMUR - Ida Hendarsih; Sri Harjunawati (Jurnal Akrab Juara, 2018)
The warehouse administrator inputs the data to the system based on inbound delivery numbers and creates an identity label of the goods according to the type of raw material and the number of drivers. Based on the lay out of each area is set into the system as BIN (line / line) printed in the form of barkode and affixed in each storage path to facilitate the quality control of raw materials that will be used to obtain quality products in accordance with the standards. This research uses descriptive qualitative method using secondary data related to raw material storage system data, layout of existing raw material warehouse, material flow in raw material warehouse, Indonesian national standardization of sweetened condensed milk quality. Furthermore, a deeper review of whether the system is quite effective and efficient to apply to the company. Keywords: Raw Material Storage, Product Quality.